High-performance poly(acrylic acid) hydrogels formed with a block copolymer crosslinker containing amino-acid derivatives. Issue 37 (12th September 2019) - Zhang, Rui; Ruan, Hengzhi; Zhou, Tianxu; Fu, Qionglong; Peng, Hongwei; Zhu, Xuedong; Yao, Yuan
Abstract : Two block copolymers containing amino-acid derivatives were employed as a macro-crosslinker to prepare high performance PAA hydrogels concluding desirable mechanical properties and self-healing abilities, as well as notch-insensitivity. Abstract : Two block copolymers containing two amino-acid derivatives, PEO- b -PLAA and PEO- b -PAAC, were fabricated through atom transfer radical polymerization (ATRP) or reversible addition–fragmentation chain transfer polymerization (RAFT). Then, they were employed as a macro-crosslinker to prepare high-performance poly(acrylic acid) (PAA) hydrogels named "P x A y " or "T y A z ". There were numerous synergistic noncovalent interactions with hydrogen bonds between the macro-crosslinker and PAA chains, as well as entanglement of polymer chains. Hence, the hydrogels exhibited desirable mechanical properties and self-healing abilities. For P x A y hydrogels, the maximum fracture elongation and fracture strength were 9800% and 120.01 kPa, respectively. Moreover, the enhanced physical interaction enabled the hydrogels to have rapid self-healing abilities without stimulation. The hydrogels showed >80% self-healing efficiency and exhibited ∼10 −3 S cm −1 electrical conductivity upon the introduction of KCl. Meanwhile, benefitting from doubling the number of carboxyl groups in the macro-crosslinker of the T y A z hydrogels compared with the P x A y hydrogels, the mechanical properties of T y A z hydrogels could be promoted further and notch-insensitivity could be observed. Tough, adhesive, self-healable, and conductive PAA hydrogels with different structures of amino-acid derivatives could aid the development of macro-crosslinkers.